ANALISA TEMPERATUR YANG TIMBUL PADA SPROKET DAN RANTAI SEPEDA MOTOR SAAT SEDANG DIJALANKAN YANG BERPENGARUH TERHADAP KEMULURAN RANTAI DENGAN MENGGUNAKAN PROGRAM NISA HEAT - Riki Candra Putra; Joko Hardono (IST AKPRIND Yogyakarta, 2018)
Chains and sprocket are transmission systems that are used to transmit power and rotation from the drive to the driven shaft. Motorcycle chains and sprocket are generally damaged due to lack of proper and correct maintenance and maintenance. The damage that occurs in general is caused by friction between the sprocket teeth and the chain that moves each other quickly, from the friction that occurs it produces heat in the metal material of the chain and sprocket. The heat generated greatly affects the performance of the material. Therefore, it is necessary to know the heat transfer analysis that occurs in friction between the chain and sprocket. Research was carried out in various places and outdoors or on the highway, when motorbikes drove at normal speed and then stopped to make temperature measurements on the surface of the gears and sprocket. Weather conditions at the time of measurement are carried out when the weather is sunny or not rainy, the aim is to facilitate measurement if it is dry or not wet due to water and analyzed using NISA-HEAT software to see temperature distribution at certain speeds and ambient temperatures certain, therefore this experiment can represent the wheel rotation of a motorcycle in conditions when it is running and when the speed of a motorcycle is changing. The heat obtained at the hottest temperature conditions of 38oC obtained by the temperature of the sprocket is 52oC at a speed of 60 km / h with a large heat transfer of 0.543 Watt. And with the increasing speed of the motorcycle to 70 km / h, the temperature of the sprocket becomes 57oC with the same ambient temperature.